User characteristics for overcoming bias and intrigue in travel searches. (22nd January 2007) - Durfee, Antonina; Medlin, B. Dawn; Cazier, Joseph A.
The internet continues to grow at an ever-increasing rate, with individuals receiving multiple responses to their online travel search queries. More than half of the individuals who search the internet are satisfied with their search results, but are unaware of the fact that the results which may appear first are most likely paid for by advertisers. In order to gain insight into the issues of bias susceptibility, an experiment was conducted to see how the attributes of trust, impatience, and search experience and search skill affected consumers' bias susceptibility. Those with a high degree of bias susceptibility are more likely to be tricked by bias information. Those with a low degree of bias susceptibility are predicted to be more likely to use multiple search interfaces to try to get more accurate and unbiased information.